Superior titanium from hybridised microstructures – A new strategy for future alloys. (December 2019) - Zafari, A.; Xia, K.
Abstract: A new strategy for future alloys by hybridising microstructures of existing alloys using selective laser melting was introduced. In particular, two existing Ti alloys were hybridised, leading to a new Ti, referred to as HYbrid Ti Alloy (HYTA). An excellent combination of high strength, work hardening and ductility was achieved, superior to conventional Ti. Further, individual properties of HYTA were manipulated via simple heat treatments, revealing great versatility. This novel approach can be applied to a vast variety of metals beyond Ti and contributes significantly to the coming era of microstructure-by-design. Graphical abstract: Unlabelled Image